Propuesta de diseño arquitectónico modular de un Centro de Salud Tipo C para la parroquia La Aurora, Daule - Montenegro Arciniega, Jamime Rebeca (2024)
The project's objective is to design a functional and comfortable public health space for all social levels in the cantonal capital of the parish of La Aurora. To achieve this, two data collection methodologies were employed to identify the specific needs of the residents. Based on this data, a list of essential medical areas was established, with maternity and pediatric areas being given priority. The design of the Type C Health Center is organized around the most critical identified needs, delineating the project into four macro-zones: outpatient, emergency, administration, and service. The outpatient area encompasses offices for various medical specialties. The emergency area is characterized by standardized spaces, with a particular emphasis on maternity and neonatology. The administration area comprises offices and other administrative areas. Finally, the service area includes machine rooms, ventilation, and other essential services...........